Penny Siopis : Time and Again. - Olivier, Gerrit (Witwatersrand University Press, 2014)
Penny Siopis engages in a variety of ways with her work of the past thirty-five years. A conversation between the artist and the editor, Gerrit Olivier, gives the reader insights into her working methods: interest in form and different genres, theoretical concerns and views on the position of art in a socio-political context.